2015
DOI: 10.1021/am509065d
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Stackable Laser-Induced Graphene Supercapacitors

Abstract: In this paper, we demonstrate that by simple laser induction, commercial polyimide films can be readily transformed into porous graphene for the fabrication of flexible, solid-state supercapacitors. Two different solid-state electrolyte supercapacitors are described, namely vertically stacked graphene supercapacitors and in-plane graphene microsupercapacitors, each with enhanced electrochemical performance, cyclability, and flexibility. Devices with a solid-state polymeric electrolyte exhibit areal capacitance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
288
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(304 citation statements)
references
References 37 publications
13
288
1
2
Order By: Relevance
“…Recently, an inexpensive laser-inducing technique at room temperature has been applied to prepare graphene on polyimide (PI) substrate, and the resulting laser-induced graphene (LIG) has been demonstrated to be a ready electrode material for supercapacitors due to its 3D porous multilayer structure. [30][31][32] This work introduces 3D LIG directly from polyimide to prepare all-solid-state, highly stretchable, and transparent MSCs, using as the active material on silicone rubber substrates. The 3D network of LIG with interdigital microelectrode structure is obtained by using laser-inducing method on PI substrate.…”
Section: Doi: 101002/smll201702249mentioning
confidence: 99%
“…Recently, an inexpensive laser-inducing technique at room temperature has been applied to prepare graphene on polyimide (PI) substrate, and the resulting laser-induced graphene (LIG) has been demonstrated to be a ready electrode material for supercapacitors due to its 3D porous multilayer structure. [30][31][32] This work introduces 3D LIG directly from polyimide to prepare all-solid-state, highly stretchable, and transparent MSCs, using as the active material on silicone rubber substrates. The 3D network of LIG with interdigital microelectrode structure is obtained by using laser-inducing method on PI substrate.…”
Section: Doi: 101002/smll201702249mentioning
confidence: 99%
“…A large variety of materials such as graphene (3)(4)(5), nanotubes (6, 7), carbide-derived carbons (CDC) (8,9), and pseudocapacitive materials (1,10,11) have been explored in micro-supercapacitors in the past 5 years. Much of the recent work focused on the use of wet processing routes (using colloidal solutions or suspensions of particles for the electrode preparation) for the development of flexible micro-devices for printable electronics (1,4,5,12). However, the wet processing methods are not fully compatible with semiconductor device manufacturing used in the electronics industry, thus hampering supercapacitor manufacturing on silicon chips.…”
mentioning
confidence: 99%
“…It was also proven that, laser induction on both sides of polyimide films multiplies electrical performance of vertically stacked supercapacitors while preserving its device flexibility. This study highlights the capability of solidstate polymeric electrolyte-based devices in exhibiting areal capacitance of more than 9 mF/cm 2 at a current density of 0.02 mA/cm 2 , which is over twice that of conventional aqueous electrolytes (Peng et al 2015). Abidin et al (2015) demonstrated that interdigital electrodes achieved maximum current response which is 5.5 A/m compared to planar electrodes which only exhibits 0.025 A/m.…”
Section: Graphene As Scaffolding For Stem Cell Based Tissue Engineeringmentioning
confidence: 71%
“…This eventually prevents graphene sheets from stacking on each other due to Van der Waals force during drying process; and acts as a binder to holds graphene sheets together. In recent studies, Wang Peng et al (2015) demonstrated the use of laser induction technology to produce laser-induced graphene from polyimide films for the fabrication of 3-D supercapacitors, namely vertically stacked graphene supercapacitors and in-plane graphene microsupercapacitors. The stacked configuration of graphene increases the energy densities of the device which leads to superconductivity.…”
Section: Graphene As Scaffolding For Stem Cell Based Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation